Development and Expert Validation of an Entrepreneurship Learning Module for Students in the Management Study Program - Miftah Ar Razy; Basyarul Ulya; Nursalimah Nursalimah (Institute of Computer Science (IOCS), 2026)
Entrepreneurship education plays an important role in developing students’ entrepreneurial competencies in higher education. However, the availability of structured and validated entrepreneurship learning modules that support competency-based learning in Management Study Programs remains limited. This study aimed to develop and validate an entrepreneurship learning module for students in the Management Study Program at Universitas Al Washliyah Labuhanbatu using the Research and Development (R&D) approach with the ADDIE model, covering the analysis, design, development, implementation, and evaluation stages. This article focuses on the module development and expert validation stages. The module was developed based on a needs analysis involving lecturers and students and was designed by integrating learning outcomes, instructional materials, case studies, project-based learning activities, and assessment instruments. The developed module was evaluated by subject matter, instructional design, media, and language experts to assess its content, presentation, instructional design, and language quality. The validation results indicated that the module was feasible in all assessed aspects, with an average score of 3.51 from instructional design experts, 3.43 from media experts, 3.42 from subject matter experts, and 3.40 from language experts, all of which were categorized as feasible. These findings indicate that the developed entrepreneurship learning module meets the quality standards required for higher education learning materials. Therefore, the module can serve as a validated learning resource to support entrepreneurship learning in the Management Study Program